2014
DOI: 10.1016/j.celrep.2014.03.065
|View full text |Cite
|
Sign up to set email alerts
|

A Mitochondrial RNAi Screen Defines Cellular Bioenergetic Determinants and Identifies an Adenylate Kinase as a Key Regulator of ATP Levels

Abstract: Summary Altered cellular bioenergetics and mitochondrial function are major features of several diseases including cancer, diabetes, and neurodegenerative disorders. Given this important link to human health, we sought to define proteins within mitochondria that are critical for maintaining homeostatic ATP levels. We screened an RNAi library targeting >1,000 nuclear-encoded genes whose protein products localize to the mitochondria in multiple metabolic conditions to examine their effect on cellular ATP levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 79 publications
(99 reference statements)
4
81
0
Order By: Relevance
“…In an effort to examine, under multiple metabolic conditions, contributions of mitochondrial proteins to cellular ATP levels, screening of an RNAi library targeting over 1000 nuclear-encoded genes corresponding to mitochondria-localized proteins revealed that AK was a key regulator of ATP levels ( Lanning et al, 2014 ). One isoform of AK (AK4), which is enzymatically inactive, in vitro interacts with mitochondrial ADP/ATP translocator ( Liu et al, 2009 ) and regulates its activity protecting cells under stress.…”
Section: Equilibration Of Adenylates Optimizes Atp Synthesis In Mitocmentioning
confidence: 99%
“…In an effort to examine, under multiple metabolic conditions, contributions of mitochondrial proteins to cellular ATP levels, screening of an RNAi library targeting over 1000 nuclear-encoded genes corresponding to mitochondria-localized proteins revealed that AK was a key regulator of ATP levels ( Lanning et al, 2014 ). One isoform of AK (AK4), which is enzymatically inactive, in vitro interacts with mitochondrial ADP/ATP translocator ( Liu et al, 2009 ) and regulates its activity protecting cells under stress.…”
Section: Equilibration Of Adenylates Optimizes Atp Synthesis In Mitocmentioning
confidence: 99%
“…The resulting MitoCarta1.0 inventory of 1098 mouse genes contained 591 curated mitochondrial components used for training, 131 proteins validated using GFP/microscopy, and 376 proteins assigned to the organelle at a 10% false discovery rate (FDR). MitoCarta1.0 has been widely used to elucidate the function of uncharacterized genes and pathways ( 6 – 9 ), including reverse genetic screens ( 8 , 10 ) and forward genetic approaches to identify genes underlying rare mitochondrial disorders ( 11 – 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…RNAi has been exploited as a valuable tool for in vivo research, and is widely used in systematic studies of gene function and large‐scale screens . Mitochondrial metabolism has been studied using RNAi screens targeting the whole genome or the MitoCarta genes (a collection of over 1000 genes encoding mitochondrial localized mammalian proteins) in several eukaryotes . For example, an RNAi screen targeting over a thousand nuclear‐encoded mitochondrial genes under different metabolic conditions revealed a link between perturbations in the electron transport chain of mitochondria and metabolic plasticity .…”
Section: Tools To Probe the Mitochondrial Metabolismmentioning
confidence: 99%
“…HOQNO has the advantage of being fluorescent in solution but quenched when bound to protein, which enables its usage in titration experiments to measure the concentration of dissociable quinol‐binding sites and their dissociation constants ( K d ) . Complex I blocker rotenone has been commonly used, sometimes in combination with other complex inhibitors such antimycin A, to restrict respiration in many mitochondrial studies …”
Section: Tools To Probe the Mitochondrial Metabolismmentioning
confidence: 99%